Study on mechanical properties of PLA/HA composite for coronary stent applications by powder processing - Chin, Man Soon (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The risen in mortality cas=use by coronary heart disease (CAD) leads to intervention of procedure such as bypass surgery and percutaneous coronary intervention (PCI) with or without stenting. Nevertheless, the idea of procedure to cure CAD is still under research and development. Under new research and development of coronary stent, it was found that the PLA-HA composite having suitable mechanical strength require by an ideal stent plus the biocompatibility of the stent itself potentially offer a better procedure to perform PCI compare with some bare metallic stent.